The slow pace for the development of tourism of the future: seductions, promises, pitfalls - De Salvo, Paola (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2019)
Sociological research is increasingly interested in tourism as a modern social and cultural phenomenon (Cohen, Cohen, 2019). In particular, the most recent studies (Bigné, Decrop, 2019, Clancy 2018, Calzati, de Salvo, 2018, Sun, Lin, 2018) have identified slowness as one of the most current characteristics of post-contemporary tourism. Slowness should not be interpreted as a phenomenon of the moment, a trend or a new tourist product, but as a philosophy of life and represents a social and global movement, which originated from the Italian Slow Food movement in the late 1980s. Slowness opposing the culture of speed doesn’t only imply slowing down but also the commitment to change one’s daily habits and behavior. These considerations will allow to highlights in the work how and if slow tourism can in the future contribute to contrast the negative externalities of uncontrolled tourism through the enhancement of behaviors, responsibilities that promote sustainability and conviviality against the decline of uniqueness of places. The essay will deepen the social category of slowness as a positive connotation of future’s tourism and not one of the many trends of postmodernity.